ANALISIS PROBLEMATIKA SUPERVISI DAN MANAJERIAL PADA KETERBATASAN MEDIA DAN MINIMNYA PEMAHAMAN GURU TERHADAP PENDEKATAN DEEP LEARNING DALAM PENERAPAN KURIKULUM MERDEKA DI RA TAHFIDZ AL-JANNAH - Nur Hidayati , Weni; Kurnia, Rita; Hasna Taqiyyah , Naila; Yufani, Berliana; Br Sihotang, Friskila; Yuliana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze supervisory and managerial problems in the implementation of the Merdeka Curriculum, particularly concerning limited learning media and teachers’ limited understanding of the deep learning approach at RA Tahfizh Al-Jannah. This research employed a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The findings reveal that academic supervision has not been optimally implemented, as it remains administratively oriented and lacks continuous reflective guidance. From a managerial perspective, limitations in strategic planning, resource management, and support for learning media provision hinder the effective implementation of the Merdeka Curriculum. Furthermore, teachers’ understanding of the deep learning approach remains conceptual and has not been fully integrated into instructional practices that promote critical and meaningful learning. The novelty of this study lies in its integrative analysis of supervision, managerial aspects, and teachers’ pedagogical competence within a Tahfizh-based RA educational setting. The study recommends strengthening reflective academic supervision, enhancing teachers’ professional competence through continuous training, and optimizing school management to support effective curriculum implementation.